Why Trade Costs Matter? - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
Trade costs are often cited as an important determinant of the volume of trade. A growing literature has documented the negative impact of trade costs on the volume of trade. Most of these studies show that integration is the resultant of reduced costs of transportation in particular and other infrastructure services in general. Direct evidence on border costs shows that tariff barriers are now low in most countries across the world. Poor institutions and poor infrastructure penalize trade, differentially across countries. Therefore, today's trade strategy goes beyond the traditional mechanisms of tariffs and quotas and includes “behind-the-border” issues, such as the role of infrastructure and governance in supporting a well-functioning trading economy.
Keywords: F1; 330; Trade Costs; Trade Facilitation